PEMIKIRAN KRITIS TENTANG BUREAUCRAT STREET LEVEL THEORY OLEH MICHAEL LIPSKY - Emy Kholifah (STIE Mandala Jember, 2013)
Many policies implemented in the field is not the same as when the policy objectives formulated and defined. One factor in why there is so, is because of the behavior of policy implementers who lack public accountability so that the change in the policy field. Michael Lipsky stated that the tendency of bureaucrats doing it because, first was due to fund operations and executive power is insufficient. The second is that bureaucrats lack empathi (altruism) to perform public service for the will serve as well as possible be based only on minimum standards and it is done only by the mechanism of 'copying' which turns out was actually done by reducing service to the community. Done if seen doing alone policy, it is referred to as the reduced form of service to the community in other words done for good imaging performance of the implementing agency for the assessment of both superiors and for the assessment of the public good. The third factor is due to a conflict with people who are considered not to be profitable. This especially will always avoided the implementers on the ground because people know that it is they who have policies and therefore the public aware tumpuhan conflict exists on implementing 'cutting edge' this. Bureaucrats implementing a 'political calculation' careful to conduct policy in good faith, if not profitable, as the executor of his position then he would do it with a policy of reducing and even minimize policy activities. The fourth factor is due to the control and the control of bureaucrats Thepeople unfavorable. Control over the implementation of the policies considered less effective for preventing behavior 'manipulative' policy implementation in the field, so it can not prevent the implementation of policies that are inconsistent with the policy objectives when it was made and approved. Factors to five, is due to the achievement of policy objectives and targets considered incompatible with the realities of implementing bureaucrats because capabilities are too high. Something that will not be achieved, it is appears to be the target of the policy, so that bureaucrats feel Thepeople will not be able to fullyimplement the policy. Another determinant factor that drives policy implementers in the field to policy reduction is the low participation of communities. With the condition of the public apathy on the implementation of the policy, so in this case as street level bureaucrats are faced with the problem independently and not many people around who can be expected to help. Problem solving is considered to be the burden of the government, the public does not think that the problem would be easily solved when there is synergy society and government. Public apathy lead implementers free to reduction and policy modifications